Microstructure and mechanical properties of laminated Nb/Ti3Al(Si)C2-TiC-Al2O3 composites; Journal of Materials Science; Vol. 60, iss. 45 - Abdulmenova A. V. Anastasiya Vladimirovna; Kashkarov E. B. Egor Borisovich; Krotkevich D. G. Dmitry Georgievich; Perevislov S. N. Sergey Nikolaevich; Travitsky (Travitzky) N. Nakhum (2025, 2025)
Title screen